Downregulation of LINC01638 lncRNA inhibits migration and invasion of pancreatic ductal adenocarcinoma cells by reducing TGF-β signaling - Lu, Huimin (Mol Med Rep, 2019)
LINC01638 is a long non-coding RNA (lncRNA) with an oncogenic role in breast cancer, while its involvement in other malignancies is unknown. This study was performed to investigate the potential role of LINC01638 in pancreatic ductal adenocarcinoma (PDAC). The expression of LINC01638 was determined via reverse transcription-quantitative polymerase chain reaction analysis, whereas the levels of transforming growth factor-β1 (TGF-β1) in plasma were measured via ELISA. Receiver operating characteristic curve analysis was conducted to determine the diagnostic value of LINC01638. Additionally, the migratory and invasive abilities of cells were evaluated via Transwell migration and invasion assays. In the present study, LINC01638 was significantly upregulated in tumor tissues compared with adjacent healthy tissues in the majority of patients with PDAC. Plasma levels of LINC01638 were significantly higher in patients with PDAC compared with in healthy controls. In effect, upregulation of plasma LINC01638 distinguished patients with PDAC from healthy controls in receiver operating characteristic analysis. Plasma levels of LINC01638 and TGF-β1 were positively correlated in patients with PDAC, but not in healthy controls. LINC01638 overexpression increased TGF-β1 expression, while silencing of LINC01638 using short hairpin RNA (shRNA) led to reduced TGF-β1 expression in a PDAC cell line. LINC01638 overexpression promoted, while shRNA silencing inhibited, migration and invasion of cell of a PDAC cell line. Treatment with exogenous TGF-β1 attenuated the inhibitory effect of LINC01638 shRNA silencing on cancer cell migration and invasion. It is concluded that LINC01638 lncRNA may be involved in the migration and invasion of PDAC cells via regulation of TGF-β1.